2021
DOI: 10.3389/fcvm.2020.592834
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in Carotid-Femoral Pulse-Wave Velocity Are Tracked by Heart-Femoral Pulse-Wave Velocity

Abstract: Background: Carotid-femoral pulse-wave velocity (cfPWV) is the reference standard measure of central arterial stiffness. However, it requires assessment of the carotid artery, which is technically challenging, and subject-level factors, including carotid artery plaque, may confound measurements. A promising alternative that overcomes these limitations is heart-femoral PWV (hfPWV), but it is not known to what extent changes in cfPWV and hfPWV are associated.Objectives: To determine, (1) the strength of the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…An alternative PWV measure is heart-femoral PWV, here the "heart" portion can be determined from an electrocardiogram and/or a phonocardiogram. We recently found good (73) (r > 0.75) agreement between hfPWV and cfPWV (r = 0.83) in 4,133 olderaged (75 [SD: 5] years) adults) (74), and we also found that these measures responded similarly (r = 0.92) to an orthostatic challenge (modified tilt-table test), a perturbation known to impact aortic arterial stiffness (75). An additional alternative is brachial-femoral PWV (bfPWV), which can be obtained using oscillometric cuffs placed around the upper arm and upper thigh.…”
Section: Pulse-wave Velocitymentioning
confidence: 62%
“…An alternative PWV measure is heart-femoral PWV, here the "heart" portion can be determined from an electrocardiogram and/or a phonocardiogram. We recently found good (73) (r > 0.75) agreement between hfPWV and cfPWV (r = 0.83) in 4,133 olderaged (75 [SD: 5] years) adults) (74), and we also found that these measures responded similarly (r = 0.92) to an orthostatic challenge (modified tilt-table test), a perturbation known to impact aortic arterial stiffness (75). An additional alternative is brachial-femoral PWV (bfPWV), which can be obtained using oscillometric cuffs placed around the upper arm and upper thigh.…”
Section: Pulse-wave Velocitymentioning
confidence: 62%
“…Whereas htPWV demonstrated strong repeated measures agreement with the referent caPWV, there was negligible repeated measures agreement between hfPWV and the referent cwPWV. This is not completely unexpected since the shorter path length of hfPWV is inherently susceptible to greater relative error than that of htPWV, therefor influencing measurement agreement to a greater extent ( 34 ). While a recent study by Ouyang did not compare PPG measures against a referent or use an acute laboratory perturbation, they did observe expected, incremental increases in PPG heart-toe PWV with both increasing age and elevated disease status ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Last, due to: (i) slightly differing path lengths (D) between PPG and referent devices and (ii) the inclusion of the pre-ejection period in the PPG-based time component (PAT) but not the referent-based time component (TT), we did not expect absolute agreement between devices. Therefore, the above steps were repeated after correcting hfPWV and htPWV using the mixed effects regression model ( 32 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, as the arterial circulation of extremities is a high resistance system at rest, the external compression of upper and lower extremity arteries did not significantly increase Aix compared to baseline; it just potentiated the high baseline resistance. However, more sophisticated experimental methods revealed earlier wave reflection even if the external compression was lower in intensity or a single extremity was affected [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%